Extraction of Teak Seeds from Fruits, their Storage and Germination - Dabral, S. L. (Indian Forester, 1976)
A technique to extract teak seed from the fruits has been described. The extracted seeds germinate and give germination as high as 50% to 79% during favourable months. Periods immediately after the break of monsoon (June or July), October, February and March have been found to be the best months for germination in Chanda region. Success of germination depends upon the relative absence of the fungal attack during different months. Seeds germinates over a wide range or temperature (25°C to 40°C) but 30°C has been found to yield good results. The germination completes in about 10-12 days. Mercury fungicide (dust formulation) has been used for preventing fungal attack on the extracted seeds during storage. The extracted seeds can be stored in air-tight containers under the cover or fungicide-dust. Seeds stored upto 2 months have so far seed tried and gave germination upto 54%. Too wet conditions cause decay of seeds soaking or seeds in water before sowing was found to be harmful.